ATOM: a touch of mathematician / Nurulhuda Taib ... [et al.] - Taib, Nurulhuda; Che Rahim, Nurul Nadiah; Mohamad Zain, Nur Fadilah; Jamil, Ezzati; Mohd Nazri, Nur Azdiyanah; Ismail, Roziah; Azizan, Ahmad Zahari (Universiti Teknologi MARA, Perak, 2020)
ATOM is a project combining the usage of technology and Matriculation Mathematics Syllabus. ATOM utilizes technology to convey Mathematics teaching at a greater speed and reachability. Students will be able to access all the necessary information by using their mobile phone and readily available apps downloaded from google play. The flow of ATOM is as follows; first, students will refer to the provided mind map to solve challenge questions regarding the topics. Then, they can check for the solution by scanning an AR (Augmented Reality) code to gain access to the video explaining step-by-step solution to the problem. The video tutorial provided will be helpful in order to provide an interesting and creative environment to learn mathematics, in contrast to the traditional and boring methods used before. Moreover, the AR code will be printed on a button badge, which students can stick to their bags or anywhere else convenient for them to carry around. No more bulky books and heavy materials needed. ATOM has been tested to certain groups of students, and they all show improvements and better performance in a certain test tailored to measure the efficiency of ATOM.